The Left-Side Bias Is Reduced to Other-Race Faces in Caucasian Individuals - Kang, Jing; Li, Chenglin; Sommer, Werner; Cao, Xiaohua (Frontiers in Psychology, 2022)
A stable marker of face perception seems to be a left-side bias, that is, a tendency to rely more on the information conveyed by the left-side of faces as compared to their right-side. Previous studies showed that the left-side bias is affected by the familiarity or experience with the face stimuli. Since lower familiarity is the hallmark of other-race relative to own-race faces, the left-side bias should be weaker for other-race faces. Further, in Chinese participants face inversion has been found to abolish the left-side bias for own-race faces. Therefore, it is of interest, whether the face inversion effect on the left-side bias also holds for non-Chinese participants and generalizes across own- and other-race faces. We tested 65 Caucasian participants in an identity similarity judgment task with upright and inverted chimeric Caucasian and Asian faces. A significant left-side bias was observed for upright own-race faces, which was abolished by face inversion, indicating that it depends on the applicability of configural processing strategies. For other-race faces, there was no left-side bias in the upright condition; interestingly, inverted presentation yielded a right-side bias. These results indicate that the left-side bias is affected by the familiarity differences between own- and other-race faces, and is a universal phenomenon for upright faces. Inverted presentation strongly reduces the left-side bias and may even revert it to a right-side bias, suggesting that the left-side bias depends on configural face processing.